Relationship between Allergic Rhinitis to Quality of Life of Students of Faculty of Medicine Universitas Sumatera Utara Batch 2018 - Anna Delinda; Andrina Rambe (Talenta Publisher, 2023)
Background: Allergic rhinitis is an inflammation mediated by Immunoglobulin E (IgE) with symptoms such as runny nose, sneezing, nasal congestion, with or without itchy nose. Although allergic rhinitis is not a dangerous disease, this disease has an impact on decreasing the quality of life of the sufferer which can interfere with daily activities. Objective: This study use to determine the relationship between allergic rhinitis and quality of life among students of the Faculty of Medicine, Universitas Sumatera Utara, batch 2018. Methods: This study used an observational analytical method with a cross-sectional study approach. The research sample was determined by simple random sampling technique and used two questionnaires, namely SFAR to assess allergic rhinitis and SF 36 to assess quality of life. Results: Based on the study, the number of allergic rhinitis sufferers from 72 students of the Faculty of Medicine, Universitas Sumatera Utara, batch 2018, 38 students suffering from allergic rhinitis. The results of data analysis using the Chi Square statistical test showed that there was a significant relationship between allergic rhinitis and quality of life, p (p value) of 0.001 (p <0.05). Conclusion: There is a relationship between allergic rhinitis and quality of life in 2018 students of the Faculty of Medicine, Universitas Sumatera Utara.